2013
DOI: 10.1128/jvi.02338-12
|View full text |Cite
|
Sign up to set email alerts
|

A Sendai Virus-Derived RNA Agonist of RIG-I as a Virus Vaccine Adjuvant

Abstract: The innate immune system is responsible for recognizing invading pathogens and initiating a protective response. In particular, the retinoic acid-inducible gene 1 protein (RIG-I) participates in the recognition of single-and double-stranded RNA viruses. RIG-I activation leads to the production of an appropriate cytokine and chemokine cocktail that stimulates an antiviral state and drives the adaptive immune system toward an efficient and specific response against the ongoing infection. One of the best-characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
116
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 45 publications
1
116
0
Order By: Relevance
“…Some of the TLR agonists have also been used to boost vaccine-induced immunity (25). Recent discoveries have suggested the cytosolic RLR/RIG-I pathway is a potential alternative target for boosting vaccine-induced immunity (26,27). 5=ppp-dsRNA is a synthetic ligand for the RIG-I receptor that, when engaged with the receptor, leads to production of type I IFN (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the TLR agonists have also been used to boost vaccine-induced immunity (25). Recent discoveries have suggested the cytosolic RLR/RIG-I pathway is a potential alternative target for boosting vaccine-induced immunity (26,27). 5=ppp-dsRNA is a synthetic ligand for the RIG-I receptor that, when engaged with the receptor, leads to production of type I IFN (5).…”
Section: Resultsmentioning
confidence: 99%
“…We found that mice im- munized with sparing doses of vaccine antigens with RIG-I ligand had long-lasting IgG and HAI antibodies sustained at significantly higher levels and were protected against a lethal pandemic virus challenge. Recently, two other studies also suggested the use of RIG-I agonists in boosting influenza immunity (27,45). However, the abilities of these molecules to offer antigen-sparing effects, induction of HAI antibodies, and protection against pandemic influenza virus challenge were not investigated in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that the 5=pppRNA sequence can be rationally modified to maximize the RIG-I response, leading to high expression of many proinflammatory and antiviral genes (24). Among the PRR-stimulating adjuvants, 5=pppRNA molecules, TLR agonists, defective interfering RNA produced by Sendai virus, and baculovirus-based vaccination vectors have all been utilized as adjuvants in several vaccine formulations, yielding promising data in preclinical studies (35,(43)(44)(45)(46)(47). Unfortunately, widespread implementation of PRR-based adjuvants in vaccines has been hampered by safety concerns, as infections and innate responses can sometimes be linked to autoimmune diseases (15).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, RNA replicon-based vaccines are amplified in the cells of the vaccinated hosts, permitting the expression of the vaccine antigen, without generating virus particles. Furthermore, in the process of amplification of their genomes, RNA replicons engage pattern recognition receptors in the host cell, adjuvanting the responses to the encoded immunogen (45)(46)(47). Although both mRNA-and replicon RNA-based vaccines were shown to elicit antigen-specific antibody and cellular immune responses against several pathogens (44,(48)(49)(50)(51), the self-amplifying nature of replicon-based vaccines is likely to result in higher levels of antigen expression and in a more effective engagement of innate immune responses than mRNA-based vaccine candidates.…”
mentioning
confidence: 99%